Use and impact of Kahoot in logistics education - Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2023)
Nowadays, the younger university students are increasingly using digital solutions, therefore teachers should turn to these solutions as well. One of the tools for this is to use an online platform instead of paper-based solutions for short end-of-class assessments. There are several such available software on the market, and this paper presents the use and results of Kahoot through two case studies. The details of the case studies also show the impact in logistics education.